2008
DOI: 10.1590/s0006-87052008000200014
|View full text |Cite
|
Sign up to set email alerts
|

Basil plants growth and essential oil yield in a production system with successive cuts

Abstract: This work studied the growth of basil plants and the effect of successive cuts on the total yield and quality of the essential oil, throughout the crop cycle. Steady increases were observed in the dry weight of the aerial part and in the essential oil yield, during the cultivation cycle. Intensive cultivation and successive cuts could improve the agronomical and industrial yield in each harvest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 8 publications
0
6
0
3
Order By: Relevance
“…Accordingly, the highest yield was obtained at the highest nitrate concentration (i.e., the 80:20). Moreover, the overall yield was higher at the first cut [ 32 , 33 ]. Nonetheless, it is interesting that yield did not significantly decrease with the 60:40 ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, the highest yield was obtained at the highest nitrate concentration (i.e., the 80:20). Moreover, the overall yield was higher at the first cut [ 32 , 33 ]. Nonetheless, it is interesting that yield did not significantly decrease with the 60:40 ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Studies carried out also on aromatic plants indicated that multiple harvests could significantly affect various traits [18][19][20][21][22] but very little is known on the metabolomics changes associated with those differences. In addition, not much is known on the effects of the cut in basil in intensive production systems [23,24], especially from the agronomic point of view [10]. In this work, we studied the difference in agronomic, physiological, and quality-related traits of basil harvested in two consecutive cuts.…”
Section: Introductionmentioning
confidence: 99%
“…Basil (Ocimum basilicum L.) is an important species of cultivated aromatic and medicinal plants belonging to the Lamiaceae (mint family). This family Lamiaceae includes about 3,200 species of annuals and nonwoody perennials which are widely distributed almost all over the temperate and tropical regions of the world [1][2][3].…”
Section: Introductionmentioning
confidence: 99%